Criterio selectivo, simultaneidad y escala en la nueva historiografía naval chilena, 1960-2022 - Thienel Kattan, Gert (Historiografías, 2024)
AbstractNaval history is one part of historiography derived from the studies of military history, perspective that is also related to political history, as it is developed mainly in the analysis of the great battles, composition of forces and leaders or strategists who fought in them, especially from the perspective of the winner. Historians who have studied the naval history of Chile have generally focused their problems on the analysis of the main naval events in which the navy has participated, the War of Independence, the War against Spain and the War of the Pacific. John Lewis Gaddis states in his book The Landscape of History. How Historians Map the Past, three capabilities that historians must have and apply: Selective criteria, simultaneity and scale. The present work studies the application of these capabilities in Chilean naval historiography, with the aim of understanding the way in these has been approached between the years 1960 and 2022, to establish possible fields that allow expanding such a current towards new approaches, methodologies, and problems.Key wordsSelective criterion, simultaneity, scale, Chilean Naval History